1985
DOI: 10.1021/i200030a020
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of a wood-derived material. Effects of moisture and ash content

Abstract: The Influence of moisture on the thermal degradation of wood waste was Investigated by pyrolyzlng ground samples in a batch fluid-bed reactor at between 320 and 470 °C in helium at 101-104 kPa. The wood samples were heated at about 300 °C/ min, so that drying and pyrolysis were simultaneous. The presence of moisture increased the yield of char by as much as 5 yield %, relative to dry samples. Moisture suppressed tar formation from demineralized samples at 470 °C but enhanced the formation of tar above and belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(59 citation statements)
references
References 3 publications
3
53
0
3
Order By: Relevance
“…Published high temperature pyrolysis experiments on biomass involve reactors such as fluid bed reactors [7,8], radiant heating techniques [9], drop tube furnaces and entrained flow reactors [10][11][12]. In the present paper, experiments are performed in a free fall reactor, also called entrained flow reactor (EFR).…”
Section: Introductionmentioning
confidence: 99%
“…Published high temperature pyrolysis experiments on biomass involve reactors such as fluid bed reactors [7,8], radiant heating techniques [9], drop tube furnaces and entrained flow reactors [10][11][12]. In the present paper, experiments are performed in a free fall reactor, also called entrained flow reactor (EFR).…”
Section: Introductionmentioning
confidence: 99%
“…Feedstock moisture is not just a question of the energy balance of biochar production, but has also the potential to define biochar properties. Although moisture can increase biochar yield at low temperatures [175], the formation of steam and subsequent steam activation might result in lower yield and partially activated biochar in high temperature production scenarios (>800 • C).…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…A special reference has to be made to explain the increase in the oil percentage for treated bagasse. It is well reported that upon deashing, both the amount of volatiles and the rate of their evolution increase [20][21][22][23]. In the presence of ash elements, the volatiles escaping undergo secondary cracking and form a soot deposit on the residual char.…”
Section: Effect Of Deashing Treatments On Pyrolysis Product Distributmentioning
confidence: 99%
“…It is appropriate to attribute this to the removal of ash from bagasse, on pretreatment. The removal or and absence of ash reduces the occurrence of ash catalysed lignin decomposition reactions forming char and water [20,21].…”
Section: Higher Heating Value (Hhv) Ph and Moisture Content Of Sugarmentioning
confidence: 99%